A Noncontact Method for the Detection and Diagnosis of Surface Damage in Immersed Structures. (19th May 2015) - Sidibe, Y.; Druaux, F.; Lefebvre, D.; Leon, F.; Maze, G.
Abstract : Detection and diagnosis method is proposed for surface damage in immersed structures. It is based on noncontact ultrasonic echography measurements, signal processing tools, and artificial intelligence methods. Significant features are extracted from the measured signals and a classification method is developed to detect the echoes resulting from surface damage in an immersed structure. The identification of the damage is also provided. Gaussian neural networks trained with a specific learning algorithm are developed for this purpose. The performance of the method is validated by laboratory experiments which indicate that this method could be suitable for the monitoring of inaccessible systems like marine turbines whose unavailability causes severe economic losses.